Coat protein gene of a PStV-Bm isolate from West Nusa Tenggara, Indonesia - Nur Indah Julisaniah; SUHARJONO; RETNO MASTUTI; ESTRI LARAS ARUMINGTYAS (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Julisaniah NI, Suharjono, Mastuti R, Arumingtyas EL. 2020. Coat protein gene of a PStV-Bm isolate from West Nusa Tenggara, Indonesia. Biodiversitas 21: 903-909. Peanut stripe virus (PStV) is a single-stranded positive-sense RNA virus capable of infecting peanut plants. An isolate of PStV (PStV-Bm) was collected from a peanut field in the Bima District, West Nusa Tenggara Province, Indonesia and the coat protein (CP) gene of this virus (CP-PStV) was extracted from the viral RNA and analyzed using reverse transcription-polymerase chain reaction methods. The CP-PStV gene of PStV-Bm was aligned with several PStV genes deposited in the Genbank (http://www.ncbi.nml.nih.gov). Based on the nucleotide sequence of the CP gene, PStV-Bm was grouped into a similar cluster with other PStVs that originated from Indonesia with a similar index, ranging from 96.8% to 98.9%. Genetic similarity (about 96.1%) was also observed between PStV-Bm and PStV from the USA. This genetic similarity indicated that viruses from adjacent regions have high genetic relationships. Some amino acid differences were observed in PStV-Bm that may be typical of this strain.